EVALUATION OF WHEAT (TRITICUM AESTIVUM, L.) SEED QUALITY OF CERTIFIED SEED AND FARM- SAVED SEED IN THREE PROVINCES OF IRAN - Khazaei, Fardin; AghaAlikhani, Majid; Mobasser, Samad; Mokhtassi-Bidgoli, Ali; Asharin, Hesam; Sadeghi, Hossein (Plant Breeding and Seed Science, 2016)
The objective of this study was to study the seed quality aspects of wheat (Triticum aestivum L.) and the extent of weed seed contamination present in wheat seeds produced in different regions of Iran. Four districts (cities), each including 12 fields (six certified seed fields and six farm-saved seed fields), were selected in each regions (provinces). One kilogram of the wheat seed sample was collected from each field for analysis in the laboratory. Wheat seeding was commonly done by farm-saved seed sourced from within the farm due to the high costs of certified seeds purchased from outside sources, followed by the low seed quality. The use of a farm-saved seed resulted in a higher germination rate and a lower mean time to germination compared with another system. The more positive temperatures experienced by mother plants could decrease the number of normal seedling and seedling length vigor index. Generally there was virtually no difference about physiological quality between certified seed and farm- saved seed sector that is related to lower quality of certified seed. The certified produced seeds had the lower number of weed seed, species and genus before and after cleaning. The highest seed purity and 1000 seed weight was obtained from the certified seed production system. The need for cleaning the farm-saved seed samples before sowing is one of the important findings of this survey.